1987
DOI: 10.1128/jvi.61.2.491-498.1987
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization escape mutants define a dominant immunogenic neutralization site on hepatitis A virus

Abstract: Hepatitis A virus is an hepatotrophic human picornavirus which demonstrates little antigenic variability. To topologically map immunogenic sites on hepatitis A virus which elicit neutralizing antibodies, eight neutralizing monoclonal antibodies were evaluated in competition immunoassays employing radiolabeled monoclonal antibodies and HM-175 virus. Whereas two antibodies (K3-4C8 and K3-2F2) bound to intimately overlapping epitopes, the epitope bound by a third antibody (B5-B3) was distinctly different as evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 28 publications
2
59
0
1
Order By: Relevance
“…PCR products and controls were electrophoresed on 0.8% agarose gels, visualized by ethidium bromide staining, and transferred to nitrocellulose [Sambrook et al, 19891. 32P-dCTP labeling of nested HCV PCR product was performed by random priming a s previously described [Stapleton and Lemon, 19871, and used for hybridization with the Southern transfer [Stapleton and Lemon, 1987;Naides et al, 19931. Specificity was confirmed by including PGEM-3Zf-5'UTR and HCV antibody negative PCR products on the agarose gel.…”
Section: Southern Blot Analysissupporting
confidence: 92%
“…PCR products and controls were electrophoresed on 0.8% agarose gels, visualized by ethidium bromide staining, and transferred to nitrocellulose [Sambrook et al, 19891. 32P-dCTP labeling of nested HCV PCR product was performed by random priming a s previously described [Stapleton and Lemon, 19871, and used for hybridization with the Southern transfer [Stapleton and Lemon, 1987;Naides et al, 19931. Specificity was confirmed by including PGEM-3Zf-5'UTR and HCV antibody negative PCR products on the agarose gel.…”
Section: Southern Blot Analysissupporting
confidence: 92%
“…HAV has been shown to possess a single conserved immunogenic neutralization site, and isolates from different parts of the world belong to a single serotype (Stapleton and Lemon, 1987;Hollinger and Emerson, 2001). Nevertheless, the study of the HAV evolution in cell culture revealed the presence of some antigenic variants in the mutant spectra that were generated even in the absence of immune selection (Sanchez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Epitope mapping using peptide antigens was little help in identifying neutralizing antigenic sites because only one of the peptides was reported to induce HAV-neutralizing antibodies [Emini et al, 1985;Wheeler et al, 1986;Gauss-Muller and Deinhardt, 19881. Two immunodominant antigenic sites within VP1 and VP3 were identified by determination of the amino acid sequence of neutralization mutants [Stapleton and Lemon, 1987;Ping et al, 19881. Both sites (residue 70 of VP3, Asp, and residue 102 of VP1, Ser) are parts of knob or loop structures predicted by the three-dimensional model and align with antigenic sites in polio and rhino virus [Luo et al, 19881. In our study, different parts of VP1 and VP3 were expressed and the antigenicity and immunogenicity of the resulting polypeptides were tested, to determine the most probable antigenic sites on these viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 depicts the overlapping HAV expression plasmids A to F and their mapping positions along the HAV genome. All plasmids contain one of two amino acids (Asp 70 in VP3 or Ser 102 in VP1) which have been described as immunodominant by analysis of neutralization escape mutants [Stapleton and Lemon, 1987;Ping et al, 19881. P-galactosidase-HAV fusion proteins were expressed after induction with IPTG, separated on SDS-PAGE, and detected by Coomassie blue staining (Table I and Fig.…”
Section: Immunization Of Rabbitsmentioning
confidence: 99%